A pedagogia da visão como amizade: uma análise exegética de Jo 1,43-51 - Silva, Nelson Maria Brechó da (2022)
The present thesis analyzes the pericope Jo 1,43-51. It indicates a reading around the pedagogy of vision as friendship in the service of life. With this, the dynamics of the verb blh,pw (to gaze), qewre,w (to contemplate) and o`ra ,w (to see). This last sense is what appears in this research on the call of Philip and Nathaniel. In the first chapter, the thematic horizon of discipleship is highlighted. In this sense, on the one hand, we see the joanina work and the dimension of discipleship. On the other hand, the hypothesis of reading the pedagogy of vision as a friendship inherent to verbs is discussed: to find, see, believe, know and follow. The second chapter deals with the exegetical issues of textual criticism; delimitation; segmentation and structure; translation; linguistic-syntactic analysis; semantic analysis; pragmatic analysis; and hermeneutic analysis. Therefore, the third chapter presents: first, Jesus who calls Philip to the following (vv. 43-44); second, the dialogue between Philip and Nathanael (vv. 45-46); third, the dialogue between Jesus and Nathanael (vv. 47-51). In the fourth and last chapter, we observe: first, the jewish tradition, above all, with Gen 28,10-22 about Jacob's dream; second, the wisdom tradition, regarding friendship in Eclo 6,5-17; third, the essene tradition present in the book of Jubilees 27,19-27, especially the re-reading of Jacob's dream with the addition of the image of the tree